The currency of truth : newsmaking and the late-socialist imaginaries of China's digital era - Chua, Emily H. C. (China understandings today., 2023)
China's news sector is a place where newsmakers, advertising executives, company bosses, and Party officials engage one another in contingent and evolving arrangements that run from cooperation and collaboration to manipulation and betrayal. Drawing on long-term ethnographic fieldwork with journalists, editors, and executives at a newspaper in Guangzhou, The Currency of Truth brings its readers into the lives of the people who write, publish, and profit from news in this milieu. The book shows that far from working as mere cogs in a Party propaganda machine, these individuals are immersed in fluidly shifting networks of formal and informal relationships, which they carefully navigate to pursue diverse goals. In The Currency of Truth, Emily H. C. Chua argues that news in China works less as a medium of mass communication than as a kind of currency as industry players make and use news articles to create agreements, build connections, and protect and advance their positions against one another. Looking at the ethical and professional principles that well-intentioned and civically minded journalists strive to uphold, and the challenges and doubts that they grapple with in the process, Chua brings her findings into conversation around "post-truth" news and the "crisis" of professional journalism in the West. The book encourages readers to rethink contemporary news, arguing that rather than setting out from the assumption that news works either to inform or deceive its publics, we should explore the "post-public" social and political imaginaries emerging among today's newsmakers and remaking the terms of their practice.